2009
DOI: 10.1161/circresaha.108.184044
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junction Remodeling and Spironolactone-Dependent Reverse Remodeling in the Hypertrophied Heart

Abstract: Abstract-Pressure overload is a common pathological insult to the heart and the resulting hypertrophy is an independent risk factor for sudden cardiac death. Gap junction remodeling (GJR) has been described in hypertrophied hearts; however, a detailed understanding of the remodeling process and its effects on impulse propagation is lacking. Moreover, there has been little progress developing therapeutic strategies to diminish GJR. Accordingly, transverse aortic banding (TAC) was performed in mice to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
73
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 37 publications
16
73
0
Order By: Relevance
“…The spatial dispersion of QT interval is restored, whereas the ST segment depression and action potential propagation and conduction velocity are considerably improved (De Mello, 2006). Similarly, spironolactone treatment prevents gap junction remodeling and restores the decreased transverse conduction velocity in a thoracic aortic constriction model (Qu et al, 2009). Likewise, eplerenone reduces fibrosis-related arrhythmias in aged mice (Stein et al, 2010).…”
Section: B Mineralocorticoid Receptor and Electrophysiological Disormentioning
confidence: 99%
“…The spatial dispersion of QT interval is restored, whereas the ST segment depression and action potential propagation and conduction velocity are considerably improved (De Mello, 2006). Similarly, spironolactone treatment prevents gap junction remodeling and restores the decreased transverse conduction velocity in a thoracic aortic constriction model (Qu et al, 2009). Likewise, eplerenone reduces fibrosis-related arrhythmias in aged mice (Stein et al, 2010).…”
Section: B Mineralocorticoid Receptor and Electrophysiological Disormentioning
confidence: 99%
“…This viewpoint is further supported by the finding that our aged 22-month-old Cx43 fl/fl control mice have lower levels of Cx43 compared with 5-month-old Cx43 fl/fl mice, resulting in increased levels of fibrosis in the aged mice (data not shown). Also, researchers have shown that long-term inhibition of the renin-angiotensin-aldosterone system of aging mice, 2 cardiomyopathic hamsters, 30 and TAC mice 31 prevents gap junction remodeling and leads to reduced levels of fibrosis. The general mechanistic view is that enhanced interstitial fibrosis leads to separation of the myocardial fibers with subsequent reduction of gap junction plaques.…”
Section: Decreased Cx43 Expression Leads To Enhanced Fibrosis and Arrmentioning
confidence: 99%
“…6 Cardiac systolic function was well compensated for the first four weeks after TAC, but gradually deteriorated thereafter, which is comparable with other studies in which decompensation also occurred after four to five weeks. [7][8][9] Systolic function was lower in TAC mice with arrhythmias (TAC+), compared with TAC mice without arrhythmias (TAC-), albeit not significant (35.0±2.7% vs. 42.2±3.6% in TAC-and TAC+, respectively; p=0.14). Interestingly, lung weight was significantly higher in TAC+, suggesting that the amount of backward failure may play a proarrhythmic role (0.261±0.043g vs. 0.178±0.005g in TAC-and TAC+, respectively).…”
Section: N T E R U N I V E R S I T Y C a R D I O L O G Y I N S T I mentioning
confidence: 99%